Hybrid precoders and combiners for mmWave MIMO systems with per-antenna power constraints - R. López-Valcarce; Nuria González-Prelcic; Cristian Rusu; R. W. Heath, Jr (IEEE Global Telecommunications Conf. (GLOBECOM), 2016)
This paper considers the design of hybrid precoders and combiners for mmWave MIMO systems with per-antenna power constraints and the additional limitations introduced by the phase-shifting network in the analog processing stage. Previous hybrid designs were obtained using a total power constraint, but in practical implementations per-antenna constraints are more realistic, specially at mmWave, given the large number of power amplifiers used in the transmit array. Assuming perfect channel knowledge, we obtain first an approximation to the alldigital solution for the precoder and the combiner given the per-antenna constraints. Then, we develop a new method for the design of the hybrid precoder and combiner which attempts to match such all-digital approximation. Simulation results show the effectiveness of the proposed approach, which performs close to the all-digital solution.
Keywords: compass; mmWave